Factors associated with artificial airway retention after skull base chordoma resection: A retrospective cohort study - Fu, Yuxuan; Yu, Yun; Cui, Yidan; Wang, Jing; Ma, Bo; Jian, Minyu; Yao, Jingxin; Jing, Longnian; Bai, Jiwei; Han, Ruquan (Frontiers in Neurology, 2022)
Background: Chordoma is a malignant bone and soft tissue tumor derived from embryonic notochord remnants, and skull base chordoma accounts for approximately 1/3 of all chordoma cases. Skull base chordoma is closely related to the brainstem and cranial nerves and has a high recurrence rate. The purpose of this study was to investigate the influence of the timing of tracheal extubation on perioperative pulmonary complications. We also aimed to explore predictors of postoperative artificial airway (AA) retention in patients with skull base chordoma. Methods: This was a single-center, retrospective cohort study. The study population included all skull base chordoma patients undergoing surgical treatment between January 2019 and December 2021 at Beijing Tiantan Hospital. The primary outcome was the incidence of postoperative pulmonary complications. Several patient characteristics were evaluated for potential associations with AA retention. Results: A total of 310 patients with skull base chordoma were enrolled. The frequency of AA retention after surgery for skull base chordoma was 30.97%. The incidence of postoperative pulmonary complications was much lower in those without AA retention (3.74% vs. 39.58%, P<0.001). Factors with the highest point estimates for the odds of AA retention included body mass index, cranial nerve involvement, maximum tumor diameter, operative method, hemorrhage volume, operative duration and intraoperative mechanical ventilation duration. Conclusions: In this retrospective cohort study, most of the factors associated with postoperative airway retention were closely related to the patient's tumor characteristics. These data demonstrate that respiratory management in patients with skull base chordoma remains an ongoing concern.